2005
DOI: 10.1046/j.1600-6143.2004.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 Pathway Suppresses Human Islet Production of Pro‐Inflammatory Cytokines and Improves Islet Graft Function

Abstract: Nonspecific inflammation is associated with primary graft nonfunction (PNF). Inflammatory islet damageis mediated at least partially by pro-inflammatory cytokines, such as interleukin-1b (IL-1b ) and tumor necrosis factor-a (TNF-a ) produced by resident islet macrophages. The p38 pathway is known to be involved in cytokine production in the cells of the monocyte-macrophage lineage. Therefore, inhibition of the p38 pathway may prevent pro-inflammatory cytokine production by resident islet macrophages and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 45 publications
4
86
1
Order By: Relevance
“…Our results indicate that the inhibitory action of adiponectin on the insular production of TNFa is dependent on the COX2-PGE 2 -TNFa pathway. COX2 and the COX2 metabolite PGE 2 are reported to have important protective roles in islet grafts due to ischemia-reperfusion injury (Matsuda et al 2005, Parazzoli et al 2012. We found that adiponectin increased expression of COX2 in cultured islets stimulated by LPS or by hypoxia-reoxygenation and the release of PGE 2 from LPS-stimulated islets.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results indicate that the inhibitory action of adiponectin on the insular production of TNFa is dependent on the COX2-PGE 2 -TNFa pathway. COX2 and the COX2 metabolite PGE 2 are reported to have important protective roles in islet grafts due to ischemia-reperfusion injury (Matsuda et al 2005, Parazzoli et al 2012. We found that adiponectin increased expression of COX2 in cultured islets stimulated by LPS or by hypoxia-reoxygenation and the release of PGE 2 from LPS-stimulated islets.…”
Section: Discussionmentioning
confidence: 63%
“…3A). PGE 2 inhibits LPS-induced production of TNFa (Matsuda et al 2005, Parazzoli et al 2012. We found that adiponectin inhibited LPS-induced production of TNFa (Fig.…”
Section: Adiponectin Inhibits Tnfa Production Through Cox2mentioning
confidence: 60%
“…Proinflammatory cytokines can induce or accelerate the recurrence of autoimmune process (16,34,35), whereas the inhibition of inflammatory pathways suppresses cytokine secretion and improves islet graft function (36). The relevance of our in vitro studies to the clinical islet transplant setting is supported by studies from Piemonti et al (18) showing an inverse correlation between MCP-1 protein expression in isolated human islets and clinical outcomes.…”
Section: Discussionmentioning
confidence: 63%
“…Human islets were incubated for 1 h with several compounds (listed below), stimulated by TNF-α (5 ng/ml) for an additional 4 h, and expression of BBC3, IL8 and TNF was measured. Compounds were selected on the basis of their specific traits: (1) etanercept, a TNF-α receptor blocker reported to improve glycaemic control in clinical trials in patients with type 1 diabetes [34]; (2) FK506, ciclosporin A and rapamycin, clinically used immunosuppressants that modulate inflammatory/immune reactions; (3) imatinib mesylate, a tyrosine kinase inhibitor that suppresses NF-κB activation and has been shown to protect islets from combined cytokines in vitro and to prevent spontaneous onset of diabetes in NOD mice [35]; and (4) SB203580, a p38 mitogen-activated protein kinase inhibitor that has been shown to prevent beta cell death, in part, by regulating TNF-α abundance [32,36,37]. Pre-incubation of islets with etanercept prevented TNF-α-induced upregulation of BBC3 (Fig.…”
Section: Resultsmentioning
confidence: 99%